KADAR INTERLEUKIN-8 KANKER PAYUDARA - Juranah Juranah; Yuyun Widaningsih; William Hamdani; Ruland DN Pakasi; Uleng Bahrun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Metastasis is the major cause of increased morbidity and mortality in breast cancer. Interleukin-8 has a contribution in the spread of the tumour cells. This study was aimed to know IL-8 levels in patients with metastasic and non metasatic breast cancer by analyzing. A cross sectional study was performed at the Dr. Wahidin Sudirohusodo, Ibnu Sina and Labuang Baji hospitals during September to December 2011. Laboratory examinations were done in the Research Centre of the Medical Faculty, University of Hasanuddin. Fiftysix (56) subjects with breast cancer were examined. The results showed that the levels of IL-8 in metastatic and non metastatic breast cancer were 13.73 pg/mL and 10.48 pg/mL respectively. Mann-Whitney test showed no significant difference of IL-8 level between them, (p=0.09). When the subjects were divided into early and advance stages, the mean levels of IL-8 were 8.035 pg/mL and 12.052 pg/mL, respectively, showing a significant difference by Mann-Whitney test (p=0.009). Based on this research, the level of IL-8 can be considered as a marker in predicting the prognosis of breast cancer. A further research in cohort studies which specific metastasis crawl method is advised by the researchers, these are suggested to allow the determination of the risk factors.